The functional capacity of plantaricin-producing Lactobacillus plantarum SF9C and S-layer-carrying Lactobacillus brevis SF9B to withstand gastrointestinal transit - Butorac, Katarina; Banić, Martina; Novak, Jasna; Leboš Pavunc, Andreja; Uroić, Ksenija; Durgo, Ksenija; Oršolić, Nada; Kukolj, Marina; Radović, Slobodanka; Scalabrin, Simone; Žučko, Jurica; Starčević, Antonio; et al. (Microbial cell factories, 2020)
We evaluated the functional capacity of plantaricin-producing Lactobacillus plantarum SF9C and S-layer-carrying Lactobacillus brevis SF9B to withstand gastrointestinal transit and to compete among the gut microbiota in vivo. Considering the probiotic potential of Lb. brevis SF9B, this study aims to investigate the antibacterial activity of Lb. plantarum SF9C and their potential for in vivo colonisation in rats, which could be the basis for the investigation of their synergistic functionality. A plantaricin-encoding cluster was identified in Lb. plantarum SF9C, a strain which efficiently inhibited the growth of Listeria monocytogenes ATCC 19111™ and Staphylococcus aureus 3048. Homology-based three-dimensional (3D) structures of SF9C plantaricins PlnJK and PlnEF were predicted using SWISS-MODEL workspace and the helical wheel representations of the plantaricin peptide helices were generated by HELIQUEST. Contrary to the plantaricin-producing SF9C strain, the S-layer-carrying SF9B strain excluded Escherichia coli 3014 and Salmonella enterica serovar Typhimurium FP1 from the adhesion to Caco-2 cells. Finally, PCR-DGGE analysis of the V2-V3 regions of the 16S rRNA gene confirmed the transit of the two selected lactobacilli through the gastrointestinal tract (GIT). Microbiome profiling via the Illumina MiSeq platform revealed the prevalence of Lactobacillus spp. in the gut microbiota of the Lactobacillus-treated rats, even on the 10th day after the Lactobacillus application, compared to the microbiota of the healthy and AlCl -exposed rats before Lactobacillus treatment. The combined application of Lb. plantarum SF9C and Lb. brevis SF9B was able to influence the intestinal microbiota composition in rats, which was reflected in the increased abundance of Lactobacillus genus, but also in the altered abundances of other bacterial genera, either in the model of healthy or aberrant gut microbiota of rats. The antibacterial activity and capacity to withstand in GIT conditions contributed to the functional aspects of SF9C and SF9B strains that could be incorporated in the probiotic-containing functional foods with a possibility to positively modulate the gut microbiota composition.